Community Participation and Development Planning in Local Government Level: A Study on the Formulation of Batu City Medium-Term Development Plan - Muluk, Mujibur Rahman Kharirul; Danar, Oscar R; Rahmawati, Lia (UI Scholars Hub, 2019)
The aim of this study was to assess the community participation process in the formulation of City Development Planning. This study developed participatory planning model to improve the effectiveness of community participation in formulation of the planning by using Soft System Methodology. Data was collected through observation, focus group discussions, and semi-structured interviews at Batu City in 2018. This study showed that Batu City needed to improve the effectiveness of public consultation forum and development planning deliberation as an instrument for community participation. This study proposed a new participatory planning model to enhance the community participation quality in the formulation of City Development Planning.